The Effect of Growth Regulating Substances Giberelin on The Growth of Cucumber (Cucumis sativus) - Weyni Iskandaria; Nindi Darmawanti; Siti Nur Annisa Boang Manalu; Indayana Febriani Tanjung; Febry Ramadhani Hasibuan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Cucumber is one of Indonesia's agricultural commodities which is in great demand by the public, but in an effort to fulfill the number of requests a way is needed to be able to increase the amount of production. One of them is the use of growth regulators in supporting the growth of cucumber seeds. Gibberellin is a growth regulator that stimulates the growth of plant stems and leaves. This study aims to determine the effect of using gibberellins on cucumber plants (Cucumis sativus). The method used in this study was direct testing with 4 treatments, namely 0 ppm, 150 ppm, 175 ppm and 200 ppm with each treatment being tested with 5 samples. The materials used in this study were cucumber seeds, sand, manure, water and the hormone gibberellin (GA3). The tools used are digital scales, measuring cups, label paper, scissors, ruler, tape measure, polybags and hoes. The results of the study found that in treatment VI (200 ppm) the hormone gibberellins had a more significant effect on the growth of cucumber seeds compared to treatments I (0 ppm), II (150 ppm and III (175 ppm).